2012
DOI: 10.2214/ajr.11.7570
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of 18F-FDG PET/CT Findings in Patients Presenting With Fever of Unknown Origin

Abstract: FDG PET/CT is a powerful tool in localizing an inciting source in patients with FUO. The high sensitivity of FDG PET/CT for diagnosing infective, inflammatory, and neoplastic processes can be exploited in this setting because these processes are often the common causes of FUO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…reported that FDG PET/ CT contributed not only to diagnosis but also to staging and pointing the biopsy site of the tumour . FDG PET/CT may also be helpful during evaluation of bilateral adrenal masses , or pancreatitis and FUO . In suspected temporal arteritis, the diagnostic role of FDG PET/CT is limited and is recommended that temporal artery biopsy performed prior to further evaluation of the FUO by PET/CT .…”
Section: Methodsmentioning
confidence: 99%
“…reported that FDG PET/ CT contributed not only to diagnosis but also to staging and pointing the biopsy site of the tumour . FDG PET/CT may also be helpful during evaluation of bilateral adrenal masses , or pancreatitis and FUO . In suspected temporal arteritis, the diagnostic role of FDG PET/CT is limited and is recommended that temporal artery biopsy performed prior to further evaluation of the FUO by PET/CT .…”
Section: Methodsmentioning
confidence: 99%
“…Because of the nonspecific nature of 18 F-FDG, it is taken up by leukocytes as well as malignant cells, thereby allowing detection of a wide range of malignant, infective and inflammatory diseases which could present with FUO. [ 1 2 ] It has shown promising results for the detection of infection in renal cysts associated with ADPKD. Pijl et al .…”
Section: Discussionmentioning
confidence: 99%
“…18 F-fluorodeoxyglucose ( 18 F-FDG) positron emission tomography-computed tomography (PET-CT) is now an integral part of fever of unknown origin (FUO) management because of its ability to demonstrate the etiology in a large proportion of cases. [ 1 ] In a patient without potential diagnostic clues, 18 F-FDG PET-CT is recommended as first-line imaging. [ 2 ] Patients with autosomal dominant polycystic kidney disease (ADPKD) are at increased risk of infection because of the presence of multiple renal cysts as well as often accompanying renal dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…The same study reported a sensitivity of 90.9% and PPV of 95.2% for FDG PET-CT in cases of PUO. [ 4 ]…”
Section: Discussionmentioning
confidence: 99%